2015
DOI: 10.1007/s10926-015-9582-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Classify Injury Severity by Diagnosis: Validation Using Workers’ Compensation and Trauma Registry Data

Abstract: Purpose Acute work-related trauma is a leading cause of death and disability among U.S. workers. Existing methods to estimate injury severity have important limitations. This study assessed a severe injury indicator constructed from a list of severe traumatic injury diagnosis codes previously developed for surveillance purposes. Study objectives were to: (1) describe the degree to which the severe injury indicator predicts work disability and medical cost outcomes; (2) assess whether this indicator adequately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Consistent with the American College of Surgeons' National Trauma Data Standard, this excluded: late effects of injuries, poisonings, toxic effects, and other external causes, superficial injuries, contusions with intact skin surface, and effects of a foreign body entering through an orifice. Consistent with work by Sears et al, 42 we also excluded burns; such injuries seem unlikely due to antidepressant use.…”
Section: Identifying Outcomessupporting
confidence: 56%
“…Consistent with the American College of Surgeons' National Trauma Data Standard, this excluded: late effects of injuries, poisonings, toxic effects, and other external causes, superficial injuries, contusions with intact skin surface, and effects of a foreign body entering through an orifice. Consistent with work by Sears et al, 42 we also excluded burns; such injuries seem unlikely due to antidepressant use.…”
Section: Identifying Outcomessupporting
confidence: 56%
“…The nature of injury is a qualitative indicator of injury severity (e.g., a fracture is generally a more severe injury than a cut or laceration); however, some nature of injury categories might encompass both minor and severe injuries (e.g., burns), limiting the usefulness of this measure. Medically based injury and illness severity classifications (e.g., Abbreviated Injury Scale, Injury Severity Score) are not available in the EPRI OHSD, but have been found to be useful for a limited group of traumatic injuries [Sears et al, ] and other qualitative proxy variables for severity such as costs could not be used because the definition of total costs varied across companies. Classification of injuries in non‐specific injury type classifications may underestimate the severity of certain injury types.…”
Section: Discussionmentioning
confidence: 99%
“…In a related validation study, we linked Washington State Trauma Registry (WTR) records with WC claims for injuries from 1998 through 2008 (N=208 522) and found that traumatic injuries classified as severe using the severe injury list (table 1) were significantly more likely than those classified as minor/indeterminate to (1) be reported to the WTR, (2) involve an early hospitalisation, (3) result in total permanent disability or death, (4) have more compensated lost work days, (5) have higher total medical costs and (6) have an unresolved claim after long-term follow-up 27. There was substantial injury severity classification agreement between WTR clinical diagnoses and WC billing diagnoses (kappa=0.75), suggesting that diagnostic information contained in billing data is adequate for this purpose 27…”
Section: Methodsmentioning
confidence: 99%